The Middle Fossa Approach for the Removal of a Trochlear Schwannoma - Andrew B. Boucher; L. Madison Michael (Case Reports in Neurological Medicine)
Objectives. Schwannomas originating from the trochlear nerve are extremely rare; only 30 cases have been reported in the literature. Many operative approaches have been utilized for lesion resection, but the advantages of the anterior transpetrosal approach are numerous and include excellent exposure, minimal extradural retraction of the temporal lobe, and minimal cerebrospinal fluid leaks. We report the second case of a trochlear schwannoma resected via the anterior transpetrosal approach. Setting. A 64-year-old male presented with 3-month history of diplopia and headaches. On physical examination, he was found to have a right fourth nerve palsy. Brain magnetic resonance imaging revealed a mass within the right ambient cistern compressing the adjacent midbrain. A right-sided anterior transpetrosal approach was used—which confirmed that the trochlear nerve entered the mass—to achieve gross total resection. Pathological examination confirmed diagnosis of schwannoma. The patient was discharged on postoperative day 3. He experienced a persistent fourth nerve palsy postoperatively with an otherwise normal neurological examination. Follow-up imaging confirmed complete removal of the tumor. Conclusion. The anterior transpetrosal approach is an excellent approach for removal of trochlear schwannomas involving the cisternal course of the trochlear nerve. It affords complete visualization of this anatomical region while introducing minimal morbidity.